Upaya Orang Tua Dalam Meminimalkan Dampak Negatif Penggunaan Smartphone Pada Anak Di Rontojali - Sadilah, Nur; Nurlinda; Rusman, Ayu Dwi Putri; Hengky, Henni Kumaladewi (FAKULTAS ILMU KESEHATAN UNIVERSITAS MUHAMMADIYAH PAREPARE, 2026)
The use of smartphones among elementary school children has increased alongside advancements in digital technology. Although smartphones offer benefits for entertainment and learning, uncontrolled use can lead to various negative effects, including physical, psychological, and social impacts. This study aims to examine the influence of smartphone use on children aged 7–12 years, the role of parents in providing guidance, and the strategies implemented to mitigate these adverse effects in Dusun Rontojali, Kecamatan Dapurang, Kabupaten Pasangkayu. The research employed a qualitative approach with a descriptive design. Data were collected through in-depth interviews, observations, and documentation, involving ten parents as primary informants. Data analysis was conducted using MAXQDA software through coding and thematic analysis. The findings revealed negative impacts such as disrupted sleep patterns, increased emotional volatility, addiction, reduced social interaction, and decreased learning motivation. Parents play a crucial role as caregivers, supervisors, role models, and motivators. Strategies applied included limiting screen time, establishing rules, providing direct supervision, and directing children toward physical or educational activities. Thus, active parental involvement through consistent implementation of these strategies proves effective in reducing the negative effects of smartphone use on children.